2015
DOI: 10.1016/j.jallcom.2014.11.151
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sensing by sol–gel grown NiO and NiO:Li thin films

Abstract: Hydrogen sensors have been prepared using nickel oxide (NiO) and lithium-doped nickel oxide (NiO:Li) thin films, deposited on glass substrates by the sol-gel spin coating technique.The surface morphology, structure, optical and electrical properties of the obtained films were studied. Hydrogen sensing results are presented for three operating temperatures (140, 160, and 180 °C) and for hydrogen concentrations ranging from 1000 to 15000 ppm in synthetic air. The NiO and NiO:Li (2% and 8% doping concentrations) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 47 publications
(50 reference statements)
1
23
0
Order By: Relevance
“…The XRD pattern exhibits numerous peaks at 2θ of 37.3 and 43.3, which are referred to (111) and (200) planes of the cubic structure of NiO, respectively, according to the JCPDS file (card no.96-900-8694). This result is in agreement with that of Sta [19]. many peaks referring to lutetium oxide at 2θ of 29.8, 34.5, and 49.6 are observed and refer to the (222), (400), and (440) planes of the cubic structure of Lu 2 O 3 , respectively, from the International Center for Diffraction (card no.…”
Section: Methodssupporting
confidence: 91%
“…The XRD pattern exhibits numerous peaks at 2θ of 37.3 and 43.3, which are referred to (111) and (200) planes of the cubic structure of NiO, respectively, according to the JCPDS file (card no.96-900-8694). This result is in agreement with that of Sta [19]. many peaks referring to lutetium oxide at 2θ of 29.8, 34.5, and 49.6 are observed and refer to the (222), (400), and (440) planes of the cubic structure of Lu 2 O 3 , respectively, from the International Center for Diffraction (card no.…”
Section: Methodssupporting
confidence: 91%
“…The deposited films exhibit XRD peaks at 2θ=37.113°, 43.219°, 62.784°, 75.469°and 79.124°corresponding to lattice planes (111), (200), (220), (311) and (222) respectively which agrees with the ICDD card no:04-033-5840. The peak width is observed to be broadened as the lithium concentration increases, which indicates that the crystalline size decreases as the lithium concentration increases [44]. The lattice constant values of the nickel oxide films deposited with different lithium concentrations are found to be nearly the same and match well with the standard value 0.418 nm (ICDD card no:04-033-5840, table 1).…”
Section: Methodsmentioning
confidence: 57%
“…and the values are presented in table 1. It is observed that the crystalline size of the nickel oxide thin films decreases as the lithium concentration increases [44]. The obtained crystalline size for the undoped NiO is 106.25 nm, LiNiO-1 is 99.51 nm, LiNiO-2 is 75.59 nm, LiNiO-3 is 49.97 nm, LiNiO-4 is 48.06 nm, LiNiO-5 is 46.14 nm.…”
Section: Methodsmentioning
confidence: 86%
“…It is well known that the electrical properties can be adjusted by doping appropriate dopants into the NiO crystal lattice. Most of the researches focused on single‐element doping for NiO films, such as K, Cu, Na, and Li, but there are limited studies on the effect of several elements co‐doping on the electrical properties of NiO thin films. The single‐element doping usually optimized only the electrical properties of NiO but deteriorated its optical properties.…”
Section: Introductionmentioning
confidence: 99%